PENGARUH BUDAYA ORGANISASI DAN ORGANIZATION CITIZENSHIP BEHAVIOR (OCB) TERHADAP KINERJA - Ridha Ramadhany; Sulaiman Asang; Hasniati (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Employee performance is strongly influenced by several factors, one of which is organizational culture. Organizational culture is built from behavior that can affect fellow employees or is called Organizational Citizenship Behavior (OCB). This study aims to describe the influence of organizational culture and Organizational Citizenship Behavior (OCB) on employee performance at the South Sulawesi Provincial Health Office. Descriptive research using quantitative methods with a sample of South Sulawesi Provincial Health Office employees taken about 73 respondents with Purposive Sampling and Accidental Sampling Techniques. The research instrument used reliability and validity tests and then univariate analysis to describe the effect of each variable and bivariate analysis was generated using Chi Squared Test and Coefficient Contingency. The study revealed that there was a very strong significant influence between organizational culture on employee performance at the South Sulawesi Provincial Health Office (P value = 0.99), there was a moderate significant effect between Organizational Citizenship Behavior (OCB) on employee performance at the Sulawesi Provincial Health Office of South Sulawesi (P value = 0.47), and there is a very strong significant effect between Organizational Culture and Organizational Citizenship Behavior (OCB) on the performance of employees of South Sulawesi Province (P Value = 0.94).